Chinese firms' export dynamics: experimental but promising. Issue 1 (2nd January 2020) - Wang, Yanling; Wei, Wei
Abstract: We study China's trade dynamics at the firm, firm–product, firm–destination and firm–product–destination levels. Using a very rich panel data on firms' export transaction from 2000 to 2006, we decompose China's export growth at the intensive and extensive margins, emphasising the roles of firms, products and destinations. We group firms, firms' products and firms' destinations into three categories as new ( successful or one-time ), continuing ( continued ) and exiting ( dropped ). We capture China's export annual growth from the perspectives of trade relationships being created, survived, or destructed. We find that exporters maintain very active strategies in their export product mix and destination portfolios. They routinely introduce new products and drop some old products in order to have a product mix for their destination markets, while also maintaining a core product strategy. A similar pattern is observed for firms' destination strategy. Our results suggest that some of the newly introduced products and/or destinations become firms' continued products and destinations, which are the driving forces for firms' year-to-year success. China's annual trade growth is primarily driven by the intensive margin, though new births always contributed a very large share to its annual export changes. In the 7-year period, it is the extensive margin that drives China's export growth.